Dios, distinto pero indistinguible : el problema de la distinción formal en el pensamiento trinitario de Adam de Wodeham (2017)
The interest of the dogma of the Trinity doesn't reside solely in its centrality to the Christian faith, but also in the philosophical challenges it poses. Indeed, the apparent absurd entailed by a God at once one and three became one of the most controversial and difficult subjects for Scholastic thinkers, who developed all sorts of analysis in order to justify it without relying on the authority of the Church. One of the most noteworthy solutions in light of its complexity and influence was the concept of the formal distinction, first proposed by John Duns Scotus (1266-1308). Through these notion, which seeks to differentiate between diverse aspects of an entity which is really unitary, Scotus was able to distinguish the divine essence from each of the persons of the Trinity "The Father, The Son and The Holy Spirit" and also from the attributes "divine wisdom and goodness, among others" without compromising God's simplicity. However, in the following years Scotus' proposal would suffer all manner of modifications which intended to restrict or eliminate it altogether. Deserving of special attention are the refinement undertaken by William of Ockham (1285-1347), who only considered it valid to distinguish between the essence and the persons; and his disciple Adam of Wodeham (c. 1298-1358), who rejects it entirely. My thesis traces the development of the concept through these three authors, with special emphasis on the latter's solution. I hope to be able to show that Wodeham's abandonment of the formal distinction embodies a commitment with the idea that, although there can be distinct aspects in God, they are impossible to distinguish; something which presents Wodeham as an original thinker with proposals of his own instead of a mere transmitter of Ockham's thought.--Tomado del Formato de Documento de Grado.